Cleo Edison Oliver, playground millionaire - Frazier, Sundee T, 1968- (Arthur A. Levine Books, an imprint of Scholastic Inc., 2016)
Fifth-grader Cleo Edison Oliver is full of money-making ideas, and her fifth-grade Passion Project is no different--but things get more complicated when she has to keep her business running, be a good listener when her best friend needs her, and deal with the bully teasing her about being adopted at the same time.